Methods of Control Land Snails "A review" - N. Ghulam, Israa (Pure Sciences International Journal of Kerbala, 2024)
This article provides a comprehensive review of how to combat land snail species, which are dangerous agricultural pests that threaten the agricultural sector and thus cause huge losses to the economy. The article explains all mechanical, chemical, biological, and even innovative methods, in addition to the development in methods and tools used and followed over time in combating snails. The article shows land snails as agricultural pests , the role of technology in control, the most important species that can be considered dangerous pests that threaten farmers and agriculture in general, and the effects of types of control on the environment and ecosystems. The article also points out the most important difficulties or obstacles facing those in charge of comprehensive control management in applying control.